Basic Salary, Remuneration and Working Conditions of Teachers from Municipal Education in Sao Paulo City - Márcia Aparecida Jacomini; Maria Angélica Pedra Minhoto (Universidade Federal do Rio Grande do Sul, 2015)
This paper characterizes the remuneration and working conditions of teachers in public schools of the city of São Paulo between 1996 and 2010. It studies the variation of the basic salary and the composition of the remuneration of teachers. It was found that the municipal education system of São Paulo stands out in terms of enrollment in the country; there is no significant increase in teacher's basic salary in comparison with the variation of the student value-year of Fundef/Fundeb; the basic salary is the item of greater financial significance in payroll; time of service is the main factor for career advancement; and the proliferation of working hours and the possibility of job accumulation became alternatives of coping with the low wages.